LEGO® as a versatile platform for building reconfigurable low-cost lab equipment - Diane N. Jung; Kailey E. Shara; Carson J. Bruns (PLoS ONE, 2025)
Laboratory equipment is critical for automating tasks in modern scientific research, but often limited by high costs, large footprints, and sustainability concerns. Emerging strategies to provide low-cost research automation tools include microfluidic devices, open-hardware devices, 3D printing, and LEGO® products. LEGO®-based equipment may be advantageous with respect to sustainability, since their inherent modularity enables disassembly, re-purposing and re-use. To explore the feasibility and cost savings of replacing conventional lab equipment with LEGO®-based alternatives, we developed and characterized the performance of three LEGO® TechnicTM laboratory tools: a syringe pump, an orbital shaker, and a microcentrifuge. These three machines share 384 pieces in common and can be constructed in series (687 pieces, <$83 USD) or in parallel (1215 pieces, <$174 USD). As a proof of concept, calcium carbonate microparticles were synthesized and isolated using the LEGO®-based and analogous commercial equipment, yielding comparatively similar results. Moreover, the ability to program custom shake profiles for the LEGO®-based orbital shaker gave access to a wider range of particle characteristics than the commercial shaker. We propose that the high cost savings and reusability of LEGO®-based lab tools extends beyond their well-established efficacy in K-12 STEM education to an attractive resource for budget-, space- and/or sustainability-conscious laboratories.